Common pulse retrieval algorithm: A fast and universal method to retrieve ultrashort pulses - Geib, Nils C.; Zilk, Matthias; Pertsch, Thomas; Eilenberger, Falk (Optica, 2019)
Many ultrashort laser pulse measurement schemes such as frequency-resolved optical gating (FROG), interferometric FROG, dispersion scan, or time-domain ptychography require a specific, iterative algorithm to retrieve pulse amplitude and phase from the measurement. In this work, we present a common pulse retrieval algorithm (COPRA) that can be applied on a broad class of measurements, including but not limited to the aforementioned ones. We demonstrate its properties in comprehensive numerical tests and show that it is fast, reliable, and accurate in the presence of Gaussian noise. For FROG, we compare it to retrieval algorithms based on generalized projections and ptychography. Furthermore, we discuss the pulse retrieval problem as a nonlinear least squares problem and demonstrate the importance of obtaining a least squares solution for noisy data. In our tests, COPRA is shown to be faster and gives more accurate results in comparison to existing retrieval algorithms. Furthermore, it can be universally applied to measurements for which no specific retrieval algorithm was known before.
CRIS-Team Scopus Importer:2023-04-20